Deconstructing Aestheticism in Oscar Wilde’s The Picture of Dorian Gray: Beauty and Moral Corruption - Nabila Yuliandini; Dini Sri Istiningdias; Misyi Gusthini (Jurnal Ilmu Sosial dan Humaniora, 2026)
This analysis of Oscar Wilde's The Picture of Dorian Gray using an aestheticism approach and decadence theory. This study aims to analyze the representation of aestheticism influenced by the thoughts of Walter Pater and the concept of decadence rooted in the ideas of Charles Baudelaire through the main character Dorian Gray. The method used is a descriptive qualitative analysis of the elements of characterization and symbolism in the novel. The analysis shows that Dorian Gray represents the extreme application of aestheticism, placing beauty, youth, and pleasure as the main goals of life without considering the moral consequences. The separation between Dorian's body, which remains beautiful, and the portrait that bears the inner decay becomes the main symbol of the paradox of aestheticism. From the perspective of decadence, Dorian's life reflects the decline of moral values, the excessive pursuit of pleasure, and the state of "spleen" in the form of boredom and existential emptiness. This study concludes that The Picture of Dorian Gray not only celebrates beauty but also critiques aesthetic life detached from ethical values.